The Role of Modern Techniques And Devices In Learning And Teaching The Arabic Language At Jamiathul Falah Arabic College East Sri Lanka - Thalib, I.M. Thalib (Bumi Lingua Edu Center, 2025)
This study aims to explore the integration of technology in teaching Arabic as a foreign language, with a particular focus on Arabic language colleges (Madrasah Education) in Sri Lanka. The study investigates the benefits of technology in facilitating the teaching and learning process, particularly in improving students’ access to information, accelerating language acquisition, and providing engaging practice opportunities. Using descriptive and analytical approaches, the study examines the current state of Arabic language teaching in Sri Lankan colleges, identifies key challenges, and highlights practical strategies adopted by Jamiathul Falah Arabic Language College. Data collection methods included observation and interviews with academics and students. Although educational technology has significant potential, many Arabic language colleges in Sri Lanka have yet to incorporate it into their teaching methodologies fully. However, Jamiathul Falah Arabic Language College is a notable exception, as it has successfully implemented technology in Arabic language teaching for several years. These findings highlight the urgent need to integrate technology into the Arabic language teaching process in Sri Lankan Arabic language colleges to improve the quality of education and address the projected shortage of qualified teachers in the future.